2020
DOI: 10.1101/2020.08.13.20174466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Infection Prevention and Control Protocols, Procedures, and Implementation in Response to the COVID-19 Pandemic in Twenty-three Long-term Care Facilities in Fulton County, Georgia

Abstract: Through infection prevention and control (IPC) site visits to 23 LTCFs in Fulton County, Georgia, comparison between the Higher- and Lower-prevalence groups revealed significant differences in PPE and Social Distancing, with five specific indicators driving these differences.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A study in the US State of Georgia reported associations between worse infection control practice and larger outbreak size. 25 Overall, there are consistent associations between care home size and the presence of an outbreak, whereas other characteristics could contribute more to outbreak size once an outbreak starts.…”
Section: Time Between First and Last Confirmed Casementioning
confidence: 85%
“…A study in the US State of Georgia reported associations between worse infection control practice and larger outbreak size. 25 Overall, there are consistent associations between care home size and the presence of an outbreak, whereas other characteristics could contribute more to outbreak size once an outbreak starts.…”
Section: Time Between First and Last Confirmed Casementioning
confidence: 85%
“…Furthermore, our intervention included outbreak measures that have been implemented to curb transmission across the United States, such as cohorting 27 and routine symptom monitoring of staff and residents, 28 universal mask policies, 29 appropriate PPE use/ensuring no PPE shortages. 30 As a result, our analysis provides additional support for the effectiveness of outbreak measures not implemented in large LTCF COVID-19 outbreaks in other jurisdictions and are comparable to recommended approaches in the United States and Canada. 2,28,[31][32][33] However, important difference exists in our approach compared to what has been reported and recommended in the United States.…”
Section: Comparison Of Related Studies In the Literaturementioning
confidence: 52%
“…In a study of LTCFs in Fulton county, USA, social distancing and maintaining maximum occupancy limit in the facilities were statistically significantly associated with lower prevalence of COVID-19 infection (p<0.05). 12 A French study by Belmin et al also found significantly lower prevalence of COVID-19 infection among LTCF residents and staff, in addition to a lower prevalence of death among residents, when staff voluntarily confine themselves to the facilities for seven or more days (p<0.001). 10 Shallcross et al also showed that non-isolation of sick residents and non-assignment of staff to care separately for infected and uninfected residents significantly increased the risk of infections among residents and staff (p<0.001).…”
Section: Isolation and Social Distancingmentioning
confidence: 94%
“…13 A total of 14,830 long term care facilities and 864,434 residents were involved in these studies. Two studies were conducted in France 8,10 and the United States 11,12 , respectively and one was conducted in the United Kingdom. 9 The only included clinical practice guideline was developed for nursing homes in Canada 13 (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation